I drank too much and now I can't walk: a case of alcohol-induced dysautonomia. Issue 8 (13th August 2021) - Assaker, Richard; El Hasbani, Georges; Antezana, Arturo Alvarez; Gamarra, Jose Vargas; Amaya-Suarez, Jose; Bertely, Christopher; Suleman, Natasha
ABSTRACT: Dysautonomia is a dysfunction of the autonomic nervous system, which mediates both sympathetic and parasympathetic functions of the human body. Alcohol has been established to affect the autonomic function through liver injury and accumulation of vasodilators. Alcohol can induce peripheral neurological diseases as well. This case report describes a patient who had a chronic history of alcoholism and uncontrolled diabetes mellitus presenting for orthostatic hypotension and peripheral neuropathy without underlying liver disease or other endocrinopathies. Although diabetes mellitus was controlled pharmacologically and risk factors for orthostatic hypotension were managed conservatively, his symptoms did not improve which indicated an alcohol-related autonomic dysfunction, shedding light on one of long-term complications of alcoholism.